Final answer:
To justify the solution, substitute the value of x back into the equation and solve for x. The value of x in the solution is -1/2.
Step-by-step explanation:
To justify the solution, we substitute the value of x back into the equation x + 3 - 2x = -1 + 1x + 5.
Let's solve it step by step:
Combine like terms on each side:
x + 3 - 2x = -1 + x + 5
-x + 3 = x + 4
Move the x term to one side:
-x - x = 4 - 3
-2x = 1
Divide both sides by -2:
-2x / -2 = 1 / -2
x = -1/2
Hence, the solution is x = -1/2.